Pelatihan Pembuatan Puding Siwalan: Inovasi Produksi Pasca Panen Buah Siwalan - Dhina Mustikaningrum; Kristiawan Kristiawan; Maimunah Maimunah; Suprayitno Suprayitno (IKIP PGRI Bojonegoro, 2022)
Women are generally spend their time with activities at the domestic level, such as cooking, taking care of children and other household activities. There are many productive activities that can be developed at the domestic level, both micro and medium scale that can be done. So it is necessary to introduce activities that can improve the family economy done by women. One of them is the innovation of post-harvest production of Tuban siwalan fruit by making siwalan pudding. The purpose of this Community Service activity is to increase the insight of the PKK of Bandungrejo Village, Plumpang Subdistrict, Tuban Regency as a partner in terms of innovation to improve the economy through training. The method used is a situational analysis assessment and training. The partner's level of understanding of the material was assessed using a pre-test and post-test. The results show that there is an increase in the understanding of the training participants on information related to the nutrition of the siwalan, the economic potential of the siwalan, the distribution of the siwalan and the lack of innovation in the processing of the siwalan. In order to increase the low selling value of the results of siwalan pudding making, it is necessary to study the packaging and marketing strategies of the siwalan pudding products. PKK must collaborate with other parties to improve their knowledge on packaging and marketing. Kaum perempuan umumnya disibukkan dengan kegiatan di level domestik, seperti memasak, mengurus anak dan pekerjaan rumah tangga lain. Banyak aktivitas produktif yang dapat dikembangkan di level domestik, baik skala mikro maupun menengah yang dapat dikerjakan. Sehingga perlu mengenalkan aktivitas yang dapat meningkatkan perekonomian keluarga yang dapat dilakukan oleh kaum perempuan. Salah satunya adalah inovasi produksi pasca panen buah siwalan khas Tuban dalam bentuk pudding siwalan. Tujuan dari kegiatan Pengabdian Kepada Masyarakat ini adalah meningkatkan wawasan PKK Desa Bandungrejo, Kecamatan Plumpang, Kabupaten Tuban sebagai mitra dalam hal inovasi untuk meningkatkan perekonomian melalui pelatihan. Metode yang digunakan adalah asesmen analisis situasi dan pelatihan. Tingkat pemahaman mitra terhadap materi dinilai menggunakan pre-test dan post-test. Hasilnya meninjukkan bahwa terjadi peningkatan pemahaman peserta pelatihan terhadap informasi gizi siwalan, potensi ekonomi siwalan, sebaran siwalan dan minimnya inovasi pengolahan siwalan. Guna meningkatkan nilai jual yang masih rendah terhadap hasil pembuatan pudding siwalan, diperlukan kajian terhadap pengemasan dan strategi marketing dari produk puding siwalan